2016
DOI: 10.1104/pp.15.01281
|View full text |Cite
|
Sign up to set email alerts
|

FamNet: A Framework to Identify Multiplied Modules Driving Pathway Expansion in Plants

Abstract: Gene duplications generate new genes that can acquire similar but often diversified functions. Recent studies of gene coexpression networks have indicated that, not only genes, but also pathways can be multiplied and diversified to perform related functions in different parts of an organism. Identification of such diversified pathways, or modules, is needed to expand our knowledge of biological processes in plants and to understand how biological functions evolve. However, systematic explorations of modules re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 56 publications
0
70
0
Order By: Relevance
“…CSI1/POM2 was in part discovered based on coexpression of the corresponding gene with the primary wall CesA genes in Arabidopsis . We therefore explored what rice CSI1/POM2 homolog displayed the closest coexpression with the rice primary and secondary wall CesAs using FamNet (Ruprecht et al, 2016). We found that the most likely candidate for this function was Os06g11990, which we referred to as CSI-like 1 (CSIL1; Supplemental Figure 8A).…”
Section: Defects In Csi1/pom2 Affect Patterning Of Cell Walls In Ricementioning
confidence: 99%
“…CSI1/POM2 was in part discovered based on coexpression of the corresponding gene with the primary wall CesA genes in Arabidopsis . We therefore explored what rice CSI1/POM2 homolog displayed the closest coexpression with the rice primary and secondary wall CesAs using FamNet (Ruprecht et al, 2016). We found that the most likely candidate for this function was Os06g11990, which we referred to as CSI-like 1 (CSIL1; Supplemental Figure 8A).…”
Section: Defects In Csi1/pom2 Affect Patterning Of Cell Walls In Ricementioning
confidence: 99%
“…Another argument that coordinated evolution might follow WGD is the observation that the evolution of traits often involves mutations in multiple genes (Bullard et al, 2010;Fraser et al, 2011;He et al, 2016;Roop et al, 2016), which makes sense given that many traits are polygenic in nature. Inquiries into the existence of such patterns of coordinated divergence in Arabidopsis thaliana (Blanc and Wolfe, 2004a;Ruprecht et al, 2016) and Saccharomyces cerevisiae (Pereira-Leal and Teichmann, 2005;Conant and Wolfe, 2006;Wapinski et al, 2007), which were mainly assessed at the expression level, have reported such cases to be rare. One exception was provided by Ihmels et al (2005), who identified a link between the evolution of anaerobic growth and transcriptional rewiring of dozens of genes following WGD in S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/255067 doi: bioRxiv preprint first posted online version 27 with an e-value cutoff of 10 -5 (21,27), while Gene Ontology terms and gene families were obtained by using the CDS sequences in TRAPID (28).…”
Section: Integration Of Nine Phytoplankton Species Into the Planet Damentioning
confidence: 99%
“…To detect conserved and duplicated modules, we applied the FamNet pipeline, which identifies co-expression neighborhoods that contain same gene families and Pfam domains (21). Briefly, when two neighborhoods of sizes A and B are compared, the number of Pfam domains and gene families (labels) in common between the two neighborhoods is counted and compared to an expected number of random neighborhoods of these sizes (21).…”
Section: Integration Of Nine Phytoplankton Species Into the Planet Damentioning
confidence: 99%
See 1 more Smart Citation